Periodic static compression of micro-strain pattern regulates endochondral bone formation - Cheng, Pengzhen; Zhao, Xueyi; Han, Meige; Zhuang, Yaping; Ning, Fenru; Hu, Yaqian; Lu, Weiguang; Miao, Sheng; Zhao, Chengxiang; Jia, Liyuan; Hao, Xue; Sun, Meng; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Developmental engineering based on endochondral ossification has been proposed as a potential strategy for repairing of critical bone defects. Bone development is driven by growth plate-mediated endochondral ossification. Under physiological conditions, growth plate chondrocytes undergo compressive forces characterized by micro-mechanics, but the regulatory effect of micro-mechanical loading on endochondral bone formation has not been investigated. In this study, a periodic static compression (PSC) model characterized by micro-strain (with 0.5% strain) was designed to clarify the effects of biochemical/mechanical cues on endochondral bone formation. Hydrogel scaffolds loaded with bone marrow mesenchymal stem cells (BMSCs) were incubated in proliferation medium or chondrogenic medium, and PSC was performed continuously for 14 or 28 days. Subsequently, the scaffold pretreated for 28 days was implanted into rat femoral muscle pouches and femoral condylar defect sites. The chondrogenesis and bone defect repair were evaluated 4 or 10 weeks post-operation.The results showed that PSC stimulation for 14 days significantly increased the number of COL II positive cells in proliferation medium. However, the chondrogenic efficiency of BMSCs was significantly improved in chondrogenic medium, with or without PSC application. The induced chondrocytes (ichondrocytes) spontaneously underwent hypertrophy and maturation, but long-term mechanical stimulation (loading for 28 days) significantly inhibited hypertrophy and mineralization in ichondrocytes. In the heterotopic ossification model, no chondrocytes were found and no significant difference in terms of mineral deposition in each group; However, 4 weeks after implantation into the femoral defect site, all scaffolds that were subjected to biochemical/mechanical cues, either solely or synergistically, showed typical chondrocytes and endochondral bone formation. In addition, simultaneous biochemical induction/mechanical loading significantly accelerated the bone regeneration. Our findings suggest that microstrain mechanics, biochemical cues, and in vivo microenvironment synergistically regulate the differentiation fate of BMSCs.Meanwhile, this study shows the potential of micro-strain mechanics in the treatment of critical bone defects.